Business Models in the Circular Economy Concepts, Examples and Theory - De Angelis, Roberta (Springer International Publishing, 2018)
This book focuses on the role of corporations in the transition towards an economy that works more in line with ecological limits. It is centred on business model innovation in the context of the circular economy, which is gaining consensus across business, policy and academic circles by proposing more resource efficient industrial processes. Interest in circular business models is growing within academic and practitioner literature yet the concept is not clearly understood, with potential negative consequences for theory building and practical implementation. Therefore, this book conceptualises circular business models and investigates their theoretical foundations in relation to the rationale for adopting them, drawing on circular economy, business model, strategic management and neo-institutional literature and secondary data.